The Impact of Finance and Business Activity of Special Economic Zone Residents on Social and Economic Development of the Region - E. M. Petrikova; L. S. Odnoral (Вестник Российского экономического университета имени Г. В. Плеханова)
On earlier stages of Russian economy establishment and development different institutional forms were built, which fostered social and economic development of territories, raising investment, attracting new technologies aimed at producing goods with high added value and cutting unemployment. The article discusses issues of special economic zone (SEZ), characterized as technical-introductory, and their impact on economic development of regions of their location. The efficiency of SEZ work was analyzed according to methodology approved by the Government of the Russian Federation. Statistics on key social and economic figures of regions proves the efficiency of SEZ work and their positive contribution to the territory development. A conclusion was drawn that SEZ in the near future can become key economic centers, which could integrate companies – SEZ residents by the cluster type and characterize the industry specialization of the region and at the same time could become a mighty stimulus for social and economic development of adjoining territories. Investment plans of companies – residents in the region and industry specialization of key companies and clusters on territories will start a new stage of building the efficient work aimed at complex SEZ development.